Badik Makassar: Kajian Visual dalam Perspektif Estetika Clive Bell - Iswan Iswan; Suherman Suherman (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to examine the visual form of the Makassar Badik through the perspective of Clive Bell's aesthetic theory (significant form). Badik, as a cultural heritage of South Sulawesi, not only functions as a means of defense but also as a symbol of identity, honor, and social values ​​of the Makassar community. This study uses a qualitative-descriptive method, with data collection techniques in the form of interviews, observations, and document studies. The data validation technique used is triangulation. The data is then analyzed qualitatively by grouping the findings into themes. The results of this study indicate that every part of the Badik, starting from the pangulu, the blade, to the banoang, is able to create a deep aesthetic and emotional experience for the community and its observers. This study confirms that the Makassar Badik not only functions as a weapon, but also as a work of art that is full of cultural, spiritual, and social values.